Harmonisasi Qanun Pedagang Kaki Lima dengan UU No. 20 Tahun 2008 dalam Perlindungan Hukum Usaha Mikro - Maula Sari; Ramadhan Ramadhan (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2026)
This study aims to analyze the harmonization between the Qanun on Street Vendors in Aceh and Law Number 20 of 2008 concerning Micro, Small, and Medium Enterprises from the perspective of legal protection for micro-enterprises. This research uses a normative juridical method with statutory and comparative approaches. Primary legal materials include Qanun of Banda Aceh City Number 3 of 2007, Qanun of East Aceh Regency Number 1 of 2020, Qanun of Lhokseumawe City Number 1 of 2014, and Law Number 20 of 2008. Secondary legal materials in the form of books, journals, and previous studies were collected through library research and analyzed qualitatively using legal interpretation and content analysis. The results show that conceptually both legal frameworks share the same objectives, yet normative tension arises because Law No. 20 of 2008 is inclusive and protective, emphasizing empowerment, while the Qanun on Street Vendors in Aceh tends to be regulative and administrative, focusing on control and sanctions. Implementation in the field leads to vertical conflicts because control measures are not balanced with the provision of alternative locations and adequate empowerment programs. Harmonization is needed through an integrative-participatory policy model that combines the principles of empowerment, community participation, and inter-governmental coordination.